RAS-pathway mutation patterns define epigenetic subclasses in juvenile myelomonocytic leukemia - Daniel B. Lipka (Nature Portfolio, 2017)
Juvenile myelomonocytic leukemia (JMML) is an aggressive disease with limited options for treatment. Here, the authors analyse the DNA methylome and mutational profile of JMML to define three subgroups with unique molecular and clinical characteristics.